PENGARUH KEBERADAAN WANITA DALAM KEANGGOTAAN DEWAN, PROFITABIILITAS, LEVERAGE, RASIO AKTIVITAS PERUSAHAAN, UKURAN PERUSAHAAN, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP RESTATEMENT LAPORAN KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Non-financial yang - Dyna Puspitasari; Indira Januarti (Diponegoro Journal of Accounting, 2014)
ABSTRACTThis study aims to analyze and provide empirical evidence about the influence of the presence of women in the membership of the board, profitability, leverage, the ratio of activity of the company, size of company, and independent board of the company's restatement of financial statements ( Empirical Study on Non - Financial Companies Listed on Stock Exchange Indonesia Year 2007-2012 ). Several previous studies showed varying results. Previous research examines the influence of gender on the restatement of financial statements using control variables, whereas this study uses several control variables in previous research that transformed into the independent variables to be tested, as well as adding variable independent board. To obtain valid results, the testing performed on each variable based on the hypothesis constructed.The samples used were selected by purposive sampling method. The samples were 137 non-financial companies that went public in the Indonesia Stock Exchange of the observation period 2007-2012. The number of samples is the result of the reduction of the population by some criteria, there are 71 companies that are not experiencing restatement and 66 companies that experienced a restatement. The method used in the study to test the hypothesis using logistic regression methods.The results indicate that the presence of women in the membership of the board, leverage, and the ratio of the company's activities affect the restatement of financial statements, while profitability, firm size, and the independent board restatement does not affect the company's financial statements.